PENGARUH EKSTRAK RIMPANG CURCUMA ALBA TERHADAP VOLUME ADENOKARSINOMA MAMMA - Moch Agus Suprijono; - Sumarno; Lirans Tia Kusuma (Majalah Ilmiah Sultan Agung, 2011)
Breast cancer is one of the most common malignant tumor found in women. A variety of modern medicine performed to treat breast cancer have many side effects and costly. Therefore it is necessary to study traditional medicine which is cheaper for the treatment of cancer. This study aims to determine the influence of rhizome extracts of Curcuma alba against the volume of breast adenocarcinoma C3H female mice. Experimental research design with pre and post test only control group design group,conducted over 21 days use 24 mice were inoculated C3H breast adenocarcinoma , further divided into 4 groups , thenmeasured its original volume . Group I was only given standard feed and aquades, the second group were given doses of extracts of rhizome of Curcuma alba 8mg / 0,2 ml, group III dose of 16mg / 0.2 ml and group IV dose of 32mg / 0.2 ml. Calculating the difference between final and initial volume performed on day 21. Data were tested with Shapiro-Wilk, and then tested with the Levene test. To compare the volume of breast adenocarcinoma pre and post samples in each group performed Pair T-test. To find significant differences between groups were tested with independent data Oneway Anova, to find significant differences between the 2 groups were tested with post hoc data. Pair test results T-test showed no significant difference between the volume of pre and post breast adenocarcinoma at doses of 16 mg / day (p <0.05) and Post Hoc test showed no significant difference in breast denocarcinoma difference in volume between pre-post control group by group dose of 16 mg / day, the dose of 8 mg / day with the dose of 16 mg / day, and between the dose of 8 mg / day with the dose 32 mg / day (p <0.05). There are the influence of rhizome extracts of Curcuma alba breast adenocarcinoma volume C3H female mice at doses of 16 mg / day.Â Key words: Curcuma alba, Breast Adenocarcinoma, Breast Adenocarcinoma Volume.